2017
DOI: 10.1002/sdtp.11899
|View full text |Cite
|
Sign up to set email alerts
|

P‐34: Compare and Model Multi‐level Stereoscopic 3D Visual Fatigue Based on EEG

Abstract: In this paper, we designed an experiment to observe changes for different fatigue level in human brain when watching random dot stereogram (RDS) using the method of EEG. The subjects were asked to watch 3D content for 30 minutes and the disparity of RDS changed every 10 seconds. During this watching task, subjects should rate their extent of fatigue during the experiment on the scale of one to five only when they felt worse or better. 30 channels electroencephalogram (EEG) signals were recorded through the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Malik et al [ 9 ] compared the EEG absolute power differences, coherence and complexity, then concluded that 3D viewing is more attractive than 2D and may cause high attention and involvement of working memory manipulations. Other researches also demonstrated the relevance between visual fatigue and disparity in stereo viewing based on EEG analysis [ 10 13 ]. Kang et al [ 14 ] developed a platform to facilitate comfortable stereo video viewing using EEG-based visual discomfort evaluation technology.…”
Section: Introductionmentioning
confidence: 99%
“…Malik et al [ 9 ] compared the EEG absolute power differences, coherence and complexity, then concluded that 3D viewing is more attractive than 2D and may cause high attention and involvement of working memory manipulations. Other researches also demonstrated the relevance between visual fatigue and disparity in stereo viewing based on EEG analysis [ 10 13 ]. Kang et al [ 14 ] developed a platform to facilitate comfortable stereo video viewing using EEG-based visual discomfort evaluation technology.…”
Section: Introductionmentioning
confidence: 99%